Fronts, baroclinic transport, and mesoscale variability of the Antarctic Circumpolar Current in the southeast Indian Ocean - Duan Yongliang; Hou Yijun; Liu Hongwei; Hu Po (2012)
Fronts, baroclinic transport, and mesoscale variability of the Antarctic Circumpolar Current (ACC) along 115A degrees E are examined on the basis of CTD data from two hydrographic cruises occupied in 1995 as a part of the World Ocean Circulation Experiment (WOCE cruise I9S) and in 2004 as a part of CLIVAR/CO2 repeat hydrography program. The integrated baroclinic transport across I9S section is (97.2x10(6)+/- 2.2x10(6)) m(3)/s relative to the deepest common level (DCL). The net transport at the north end of I9S, determined by the south Australian circulation system, is about 16.5x10(6) m(3)/s westward. Relying on a consistent set of water mass criteria and transport maxima, the ACC baroclinic transport, (117x10(6)+/- 6.7x10(6)) m(3)/s to the east, is carried along three fronts: the Subantarctic Front (SAF) at a mean latitude of 44A degrees-49A degrees S carries (50.6x10(6)+/- 13.4x10(6)) m(3)/s; the Polar Front (PF), with the northern branch (PF-N) at 50.5A degrees S and the southern branch (PFS) at 58A degrees S, carries (51.3x10(6)+/- 8.7x10(6)) m(3)/s; finally, the southern ACC front (SACCF) and the southern boundary of the ACC (SB) consist of three cores between 59A degrees S and 65A degrees S that combined carry (15.2x10(6)+/- 1.8x10(6)) m(3)/s. Mesoscale eddy features are identifiable in the CTD sections and tracked in concurrent maps of altimetric sea level anomalies (SLA) between 44A degrees-48A degrees S and 53A degrees-57A degrees S. Because of the remarkable mesoscale eddy features within the SAF observed in both the tracks of the cruises, the eastward transport of the SAF occurs at two latitude bands separating by 1A degrees. Both the CTD and the altimetric data suggest that the mesoscale variability is concentrated around the Antarctic Polar Frontal Zone (APFZ) and causes the ACC fronts to merge, diverge, and to fluctuate in intensity and position along their paths.